Seasonal alterations in host range and fidelity in the polyphagous mirid bug, apolygus lucorum (Heteroptera: Miridae) - Pan, Hongsheng; Liu, Bing; Lu, Yanhui; Wyckhuys, Kris A.G. (Public Library of Science, 2015)
In herbivorous insects, host plant switching is commonly observed and plays an important role in their annual life cycle. However, much remains to be learned about seasonal host switching of various pestiferous arthropods under natural conditions. From 2006 until 2012, we assessed Apolygus lucorum (Meyer-Dür) host plant use in successive spring, summer and winter seasons at one single location (Langfang, China). Data were used to quantify changes in host plant breadth and host fidelity between seasons. Host fidelity of A. lucorum differed between seasons, with 87.9% of spring hosts also used in the summer and 36.1% of summer hosts used in winter. In contrast, as little as 25.6% host plant species were shared between winter and spring. Annual herbaceous plants are most often used for overwintering, while perennial woody plants are relatively important for initial population build-up in the spring. Our study contributes to an improved understanding of evolutionary interactions between A. lucorum and its host plants and lays the groundwork for the design of population management strategies for this important pest in myriad crops.